2022
DOI: 10.21470/1678-9741-2022-0143
|View full text |Cite
|
Sign up to set email alerts
|

Skin Closure After No-Touch Saphenous Vein Harvest: Strategies to Minimize Wound Complications

Abstract: The no-touch saphenous vein with surrounding pedicle tissue harvesting technique preserved endothelium and vessel wall integrity and demonstrated improved long-term saphenous vein conduit patency that was comparable to internal thoracic artery conduit patency. Despite improved saphenous vein conduit patency rates, there is a possibility that no-touch saphenous vein harvest may increase wound complication rates by increased tissue disruption, including venous and lymphatic channels. Comprehensive strategies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
0
0
Order By: Relevance
“… 13 , 14) To minimize the development of wound complications after NT SV harvest, preoperative evaluation of lower limb vascular status, selection of an adequate vein, creation of a precise incision, careful harvest, placement of a drain in the vein harvest site, and meticulous skin wound closure were performed in this study. 16) …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 13 , 14) To minimize the development of wound complications after NT SV harvest, preoperative evaluation of lower limb vascular status, selection of an adequate vein, creation of a precise incision, careful harvest, placement of a drain in the vein harvest site, and meticulous skin wound closure were performed in this study. 16) …”
Section: Discussionmentioning
confidence: 99%
“…13,14) To minimize the development of wound complications after NT SV harvest, preoperative evaluation of lower limb vascular status, selection of an adequate vein, creation of a precise incision, careful harvest, placement of a drain in the vein harvest site, and meticulous skin wound closure were performed in this study. 16) We believe that prevention of serosanguinous fluid and blood collection and alleviating dead space by using an appropriate drain are mandatory for decreasing the potential risk of wound complications. Another study after endoscopic SV harvesting also showed that the use of a high vacuum leg drain was associated with decreased hematoma formation, higher patient satisfaction, and reduced antibiotic administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations